2022
DOI: 10.1021/acs.jcim.2c00731
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Antileishmanial Compounds: General Model, Preparation, and Evaluation of 2-Acylpyrrole Derivatives

Abstract: In this work, the SOFT.PTML tool has been used to pre-process a ChEMBL dataset of pre-clinical assays of antileishmanial compound candidates. A comparative study of different ML algorithms, such as logistic regression (LOGR), support vector machine (SVM), and random forests (RF), has shown that the IFPTML-LOGR model presents excellent values of specificity and sensitivity (81–98%) in training and validation series. The use of this software has been illustrated with a practical case study focused on a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…15 N-Pyridinyl-2-acyl pyrrole 11, reported in an interesting study by Santiago et al, showed activity against L. amazonensis and L. donovani promastigotes with IC 50 of 16.9 mM and 7.8 mM, respectively. 16 The last example of a pyrrolecontaining antileishmanial agent is compound 12 that showed IC 50 = 0.33 mg mL −1 (1.2 mM) against L. major promastigotes. 17 Among several strategies for the discovery of new hit and/or lead compounds, molecular hybridization has proven to be a good option.…”
Section: Introductionmentioning
confidence: 99%
“…15 N-Pyridinyl-2-acyl pyrrole 11, reported in an interesting study by Santiago et al, showed activity against L. amazonensis and L. donovani promastigotes with IC 50 of 16.9 mM and 7.8 mM, respectively. 16 The last example of a pyrrolecontaining antileishmanial agent is compound 12 that showed IC 50 = 0.33 mg mL −1 (1.2 mM) against L. major promastigotes. 17 Among several strategies for the discovery of new hit and/or lead compounds, molecular hybridization has proven to be a good option.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the observed correlations among data derived from various antioxidant activity assays, the adoption of a multitask learning strategy has the potential to enhance the predictive capabilities of the model. Multitask models for quantitative structure–biological effect relationships (mtk-QSBER) have been used to simultaneously predict activity, toxicity, and ADME end points across a range of biological targets and assay protocols. For instance, these models have been used to identify new lead compounds with antileishmanial properties, design chemicals with dual pan-antiviral and anticytokine storm profiles, and discover multistrain inhibitors for antituberculosis therapy. The mtk-QSBER models provide new perspectives and tools for drug design and biological effect prediction.…”
Section: Introductionmentioning
confidence: 99%